Penyuluhan Pijat untuk Mengatasi Kembung pada Bayi di Klaten - Lusinta Agustina; Sih Rini Handajani (Kolaborasi: Jurnal Pengabdian Masyarakat, 2023)
Introduction: Infancy is an important time for the fastest growth and development. One of the influencing factors grow flower baby is massage baby. Massage or touch is the most basic thing related with skin man for feel safe, comfortable and loved. Touch impact positive for growth and development baby. Massaging is also possible help baby in overcome distraction digestion like bloating and colic. Massage expedite circulation air in the stomach so that help expel trapped gas stomach. Objective: Service activities public This aim For increase knowledge Mother about massage baby For overcome stomach bloated and able to practice massage baby at home. Methods: methods devotion public with activity counseling that is gift information related with massage baby overcome stomach bloated, then next with accompaniment practice massage baby. Results: results activity devotion public This is increasing knowledge Mother about massage baby for overcome stomach bloating and mom can do massage baby. Conclusion: mother own good knowledge about massage baby for overcome stomach bloating in babies and can practice massage baby in a manner independent